2012
DOI: 10.3109/13697137.2012.698432
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture improves sleep in postmenopause in a randomized, double-blind, placebo-controlled study

Abstract: Acupuncture was effective in improving reported sleep quality and quality of life in postmenopausal women with insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 37 publications
1
32
1
3
Order By: Relevance
“…Although previous studies have demonstrated that acupuncture might be an alternative therapy for insomnia [18, 19], our data indicated that insomnia patients typically sought acupuncture treatment for injury, poisoning, and diseases of the musculoskeletal system and connective tissue. Following insomnia, diseases of the digestive system were the second most frequent disease category for TCM visits by CAHCHP patients.…”
Section: Discussioncontrasting
confidence: 69%
“…Although previous studies have demonstrated that acupuncture might be an alternative therapy for insomnia [18, 19], our data indicated that insomnia patients typically sought acupuncture treatment for injury, poisoning, and diseases of the musculoskeletal system and connective tissue. Following insomnia, diseases of the digestive system were the second most frequent disease category for TCM visits by CAHCHP patients.…”
Section: Discussioncontrasting
confidence: 69%
“…Contradictory results have been published by randomized controlled trials (RCTs) on the effects of acupuncture on alleviating menopause-related sleep disturbances. [6][7][8][9][10] Furthermore, considering that sleep disturbances are strongly associated with the levels of sex hormone levels, researchers have studied the response of sex hormones to acupuncture in women experiencing menopause-related symptoms and have published conflicting results. [11][12][13] However, the effect of acupuncture on menopause-related sleep disturbances and whether the effectiveness of acupuncture in managing menopause-related sleep disturbances is affected by acupuncture-induced changes in sex hormones levels remain unclear.…”
mentioning
confidence: 99%
“…In the studies noted that methods such medicinal herbs, acupuncture and exercises are used to improve sleep disorders (Taavoni et al, 2013;AlAkoum et al, 2009;Mansikkamaki et al, 2012;Hachul et al, 2012;Newton et al, 2014). Several studies determined a significant improvement in sleep quality for women who had taken part in regular aerobic exercise for six months (Mansikkamaki et al, 2012;Newton et al, 2014).…”
Section: Sleep Problemsmentioning
confidence: 99%
“…These changes and symptoms including vasomotor changes, emotional changes, sleep problems, changes in the urogenital system problems, muskular and skeletal problems and cardiovascular problems occur as a result of estrogen decline and they manifest as cycle disorders (Taşkın, 2012). Studies have been carried out which suggested that alternative methods are thought to be effective in improving menopausal symptoms (Al-Akoum et al, 2009;Mansikkamaki et al, 2012;Hachul et al, 2012;Taavoni et al, 2013;Newton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%